<span>The <u>correct answers</u> are:
x=-3 and x=-8.
Explanation<span>:
We can first write this in standard form, ax</span></span>²<span><span>+bx+c=0. To do this, we will add 11x to both sides:
x</span></span>²<span><span>+24+11x=-11x+11x
x</span></span>²<span><span>+11x+24=0.
Now we can factor this. Look for factors of c, 24, that sum to b, 11. Factors of 24 are:
1 and 24 (sum 25)
2 and 12 (sum 14)
3 and 8 (sum 11)
4 and 6 (sum 10).
The factors we need are 3 and 8, since they sum to 11. This gives us factored form:
(x+3)(x+8)=0.
Using the zero product property, we know that in order to have a product of 0, one or both of the factors must be 0. This means we have:
x+3=0 or x+8=0.
Solving the first equation:
x+3-3=0-3
x=-3.
Solving the second equation:
x+8-8=0-8
x=-8.</span></span>
Answer:
Step-by-step explanation:
The total surface area of the sphere = 2πr²
Total surface area of the cylinder = 2πr²+2πrh
Total surface area of the solid = 4πr²+2πrh
r is the radius of the sphere and the cylinder
h is the height of the cylinder
Total surface area of the solid = 2πr(r+h)
If the total height of the solid is 18 cm, then r+h = 18cm
Given the Total surface area of the solid = 205π cm
205π = 2πr(r+h)
205π = 2πr(18)
205π = 36πr
205 = 36r
Divide both sides by 36
205/36 = 36r/36
r = 5.69cm
Since r+h = 18cm
5.69+h = 18
h = 18-5.69
h = 12.31cm

<u>Given expression is </u>

can be rewritten as

We know,

And

So, using this identity, we


can be further rewritten as





<u>Hence, </u>

Answer:
Step-by-step explanation:
x^2 + 48^2 = 50^2
x^2 + 2304 = 2500
x^2 = 196
x = 14
answer is a